Gαq modulates the energy metabolism of osteoclasts - Chakraborty, Sushmita; Handrick, Bianca; Yu, Dayoung; Bode, Konrad A.; Hafner, Anna; Schenz, Judith; Schaack, Dominik; Uhle, Florian; Tachibana, Taro; Kamitani, Shigeki; Vogl, Thomas; Hieke-Kubatzky, Katharina (Frontiers in Cellular and Infection Microbiology, 2023)
IntroductionThe bacterial protein toxin Pasteurella multocida toxin (PMT) mediates RANKL-independent osteoclast differentiation. Although these osteoclasts are smaller, their resorptive activity is high which helps in efficient destruction of nasal turbinate bones of pigs.MethodsThe proteome of bone marrow-derived macrophages differentiated into osteoclasts with either RANKL or PMT was analysed. The results were verified by characterizing the metabolic activity using Seahorse analysis, a protein translation assay, immunoblots, real-time PCR as well as flow cytometry-based monitoring of mitochondrial activity and ROS production. A Gαq overexpression system using ER-Hoxb8 cells was used to identify Gαq-mediated metabolic effects on osteoclast differentiation and function.ResultsPMT induces the upregulation of metabolic pathways, which included strong glycolytic activity, increased expression of GLUT1 and upregulation of the mTOR pathway. As OxPhos components were expressed more efficiently, cells also displayed increased mitochondrial respiration. The heterotrimeric G protein Gαq plays a central role in this hypermetabolic cell activation as it triggers mitochondrial relocalisation of pSerSTAT3 and an increase in OPA1 expression. This seems to be caused by a direct interaction between STAT3 and OPA1 resulting in enhanced mitochondrial respiration. Overexpression of Gαq mimicked the hypermetabolic phenotype observed for PMT-induced osteoclasts and resulted in higher glycolytic and mitochondrial activity as well as increased bone resorptive activity. In addition, rheumatoid arthritis (RA) patients showed an increase in GNAQ expression, especially in the synovial fluid.DiscussionOur study suggests that Gαq plays a key role in PMT-induced osteoclastogenesis. Enhanced expression of GNAQ at the site of inflammation in RA patients indicates its pathophysiological relevance in the context of inflammatory bone disorders.
Im Titel ist alpha als griechischer Buchstabe dargestellt
Im Titel ist "q" bei "Gα" tiefgestellt
Gesehen am 17.01.2023